Size effect in reinforced concrete beams with short shear span and without stirrups - Ince, Ragip; Arslan, Abdussamet (My University, 2000)
For the to design of reinforced concrete beams with no stirrups, different equations have been formulated by researchers. These equations either are on the side of extreme safety or do not include the effect of size they only take into consideration the cracking loads. However, a cracked reinforced concrete zone has a greater load bearing capacity than the cracking load (especially for beams with a short shear span). In addition, the phenomena of size effect must be taken into account due to mechanisms which occur in a cracked zone. Because of these factors four-point-bending tests are carried out on reinforced concrete beams without shear reinforcements which are geometrically similar (size range 1:4) and the shear span to effective depth ratio is 1.5 (a/d=1.5). Data obtained from the test results are analysed by means of deterministic size effect theories and the results are compared with the design equations in the literature. The research work presented in this paper shows that a simple and reliable equation can be found and proposed for the design of reinforcement concrete beams in the case of a short shear span without stirrups.
Kesme acikligi kisa kayma donatisiz betonarme kirislerde boyut etkisi
Keywords: Bazant's size effect theory; Carpinteri's size effect theory; Design; Reinforced concrete; Shear strength